Efectos de las estrategias de precios en la percepción del valor del producto en el comportamiento del consumidor del sector retail de la ciudad de Loja - Cueva Dávila, Rony Mauricio (2024)
The research focuses on analyzing the effects of pricing strategies on the perception of product value on consumer behavior in the retail sector in the city of Loja. The aim is to identify the predominant pricing strategies and understand the variability in value perception among consumers, considering three key variables; pricing strategies, value perception and consumption dimensions. To gather information on the influence of pricing strategies, 140 observations were carried out in micro and small enterprises, stratified by consumption dimensions. In addition, a survey was applied to 383 Lojano consumers to evaluate the perception of value, which was considered as a conclusive exploratory research. The results were analyzed using IBM SPSS, revealing differences and similarities in pricing strategies in the retail sector, highlighting strategies for new products, product line, promotional and segmentation strategies. It was observed that 85% of the companies implement neutral price strategies, 68.6% use marked prices, 62.1% apply random discounts and 60% offer volume discounts, considered influential in the sector. Regarding the perception of value, several aspects were analyzed, where it was mainly highlighted that the sector where high levels of evaluation were shown is the food sector with 52%. On the other hand, quality and benefits in relation to price emerged as relevant factors during the purchase process, represented by 94.8%, being more significant in the food sector. In terms of consumer behavior, those with low perception sought alternatives in 52.5%, while those with high perception showed 52.5% willingness to repurchase and 47.5% willingness to recommend the product to others.